Penggunaan telehealth sebagai media edukasi dan dampaknya terhadap kualitas hidup pasien stroke: A systematic review - Dewi, Dwijayanti Mei Ana; Sari, Yunita; Awaludin, Sidik (Holistik Jurnal Kesehatan, 2025)
Background: Stroke is the leading cause of disability and the second leading cause of death worldwide. Effective rehabilitation is crucial for improving the quality of life of stroke patients. Digital technology, including telehealth, has emerged as an innovative tool for stroke rehabilitation and patient education. However, its effectiveness in enhancing stroke patients' quality of life remains to be fully explored. Purpose: To analyze the influence of using telehealth as an educational medium and its impact on the quality of life of stroke patients. Method: This systematic review followed PRISMA guidelines. A literature search was conducted using EBSCO, Google Scholar, IJSR, PubMed, and ScienceDirect databases with the keywords “telehealth,” “mobile education,” “stroke,” and “quality of life.” Of the 966 articles identified, 12 met the inclusion criteria and were analyzed descriptively. Results: Telehealth interventions positively impact stroke patients' quality of life by improving medication adherence, physical rehabilitation, and disease management. Various telehealth approaches, including mobile applications, video conferencing, and telemedicine systems, enhance motor function, self-efficacy, and reduce anxiety and depression. However, their effectiveness is influenced by digital literacy and healthcare provider involvement. Conclusion: Telehealth holds great potential as an educational tool in stroke rehabilitation, promoting better treatment adherence and overall well-being. However, socio-cultural factors, technological access, and digital literacy must be considered. Suggestion: Further research is needed to optimize technology-based educational strategies for stroke rehabilitation.   Keywords: Mobile Education; Quality of Life; Stroke; Telehealth.   Pendahuluan: Stroke merupakan penyebab utama kecacatan dan penyebab kematian kedua di dunia. Rehabilitasi yang efektif sangat penting untuk meningkatkan kualitas hidup pasien stroke. Teknologi digital, termasuk telehealth, telah berkembang sebagai alat inovatif dalam rehabilitasi dan edukasi pasien. Namun, efektivitasnya dalam meningkatkan kualitas hidup pasien stroke masih perlu diteliti lebih lanjut. Tujuan: Untuk menganalisis pengaruh penggunaan telehealth sebagai media edukasi dan dampaknya terhadap kualitas hidup pasien stroke. Metode: Systematic literature review ini mengikuti pedoman PRISMA. Pencarian literatur dilakukan melalui database EBSCO, Google Scholar, IJSR, PubMed, dan ScienceDirect dengan kata kunci “telehealth,” “mobile education,” “stroke,” dan “quality of life.” Dari 966 artikel yang diidentifikasi, 12 artikel memenuhi kriteria inklusi dan dianalisis secara deskriptif. Hasil: Intervensi telehealth berdampak positif terhadap kualitas hidup pasien stroke dengan meningkatkan kepatuhan terhadap pengobatan, rehabilitasi fisik, dan manajemen penyakit. Berbagai metode telehealth, termasuk aplikasi seluler, telekonferensi video, dan sistem telemedicine, terbukti meningkatkan fungsi motorik, efikasi diri, serta mengurangi kecemasan dan depresi. Namun, efektivitasnya dipengaruhi oleh literasi digital dan keterlibatan tenaga kesehatan. Simpulan: Telehealth memiliki potensi besar sebagai media edukasi dalam rehabilitasi stroke dengan meningkatkan kepatuhan terhadap pengobatan dan kualitas hidup pasien. Namun, faktor sosio-kultural, akses terhadap teknologi, dan literasi digital perlu diperhatikan. Saran: Penelitian lebih lanjut diperlukan untuk mengoptimalkan strategi edukasi berbasis teknologi dalam rehabilitasi stroke.   Kata Kunci: Kualitas Hidup; Media Edukasi, Stroke; Telehealth.